Synergistic Enhancement of Cauliflower Yield: Harnessing Phosphate-Solubilizing Bacteria and Nitrogen-Fixing Microbes for Sustainable Agriculture - Parmeshwar Singh; Anju Meshram; Ravi Kant Singh; Laiq ur Rahman; Vivek Kumar Morya (Journal of Pure and Applied Microbiology)
Cauliflower (Brassica oleracea var. botrytis) is a crucial cash crop predominantly consumed as a vegetable. High-yielding varieties are favored to maximize productivity and income, but they require substantial nutrients, leading to heavy reliance on chemical fertilizers and pesticides. This practice poses health risks and causes environmental pollution. Adequate nutrient availability, particularly for phosphorus (P) and nitrogen (N), is essential for optimal cauliflower growth. Phosphate-solubilizing bacteria (PSB) enhance P availability by solubilizing insoluble phosphates, whereas nitrogen-fixing microbes (NFM) convert atmospheric nitrogen into usable forms. These microbial inoculants are eco-friendly alternatives to chemical fertilizers, which promote nutrient availability and plant growth. The purpose of this study was to separate, identify, and describe PSB from the soil of the cauliflower rhizosphere in the Uttar Pradesh district of Lucknow, Unnao, and Kanpur. Selected PSB isolates were screened, characterized using 16S rRNA, and evaluated for their phosphate solubilization capacity at different phosphorus concentrations. The results showed increased phosphate solubilization up to 72 h, with tricalcium phosphate (TCP) solubilized most effectively at 500 ppm and rock phosphate (RP) or bone meal (BM) at 250 ppm. Bacillus pumilus exhibited the highest phosphate solubilization ability. This research highlights the potential of PSB and NFM as sustainable solutions for reducing chemical fertilizer dependency, enhancing soil fertility, and promoting cauliflower growth, thereby offering a promising approach to sustainable agriculture.